Breemie Stanes, Aberdeenshire: A note on a modern stone circle. Issue 1 (March 2015) - Bradley, Richard; Watson, Aaron
Abstract : This note describes a stone circle in north-east Scotland which was inspired by prehistoric prototypes but built in 2004. It considers the circumstances in which the monument was constructed and used, the intentions of the original designer and its relationship to authentic examples in the same region. The circle is a particularly close copy of ancient structures in the vicinity, yet it was conceived by a modern shaman and its layout was apparently influenced by contacts with supernatural powers.